Violación del debido proceso por efecto de la aplicación de la justicia indígena. - Lucero Bonilla, Diana Lorena (2015)
The present thesis, the theme: "Violation of Due Process due to the application of Indigenous Justice", Consist of six chapters in Which concepts of the subject under investigation are detailed. In the introduction, a summary of the application of Due Process in cases of application of Indigenous Justice in the problematization is made, the application of Indigenous Justice Focuses on the overall and specific objectives To Stated, the hypothesis, independent and dependent variables and resources are detailed. In the theoretical framework, Consisting of background research, rationale: Doctrine, Jurisprudence, Law and Comparative Law in respect of the subject matter, Where the Constitution of the Republic reference to different laws and is Especially builds applicability of Due Process. In the metodología, methods used are determined to, the Applied techniques in the field, surveys Applying Citizens of Canton Quevedo, and Interviews with lawyers Such results tabulation, analysis and processing Were Performed data, reporting of research and hypothesis testing was developed. The Conclusions and recommendations and legal Proposed Reforms are made to art. 345 of the Code of Judicial Function.